ANALISIS EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI KEBUN BENIH PADI PADA BALAI BENIH TANAMAN PANGAN DAN HORTIKULTURA WILAYAH SEMARANG - Khoerul Amri (Economics Development Analysis Journal, 2014)
Rice as staple food most of Indonesian people as well as a threat to food tenacity. The use of certified seeds is one way to increase productivity. Balai Benih Tanaman Pangan dan Hortikultura (BBTPH) Wilayah Semarang as one of the technical unit in terms of seed production showed a decline in the last few years. The decrease may result due to the use of factors of production is inefficient. The purpose of this study is: (1) analyze the factors that affect the production of rice seed production orchard in BBTPH Semarang area, (2) analyze the technical efficiency, (3) analyze the allocative efficiency (4) analyzing the economic efficiency, (5) analyzing rate of return to scale in rice seed orchard BBTPH Semarang area. The data used in this study are panel data. The analysis tools are production function with stochastic frontier approach. Based on the obtained data processing technical efficiency value of 85%, 12.15 allocative efficiency and economic efficiency of 10.32. The results showed that fertilizer and seed variables have positive and significant. Values return to scale of 7.67 indicates that production activities are increasing returns to scale.©